PENGARUH INVESTASI HUMAN CAPITAL IKLIM ORGANISASI TERHADAP KINERJA KAYAWAN DAN DAMPAKNYA TERHADAP KINERJA ORGANISASI PENGELOLAAN HUTAN PRODUKSI SECARA LESTARI (KINERJA PHPL) PT. KALIMANTAN SATYA KENCANA (PT. KSK) - Nandang Supriantna; Sugito Efendi; Edi Sugiono (Institut Ilmu Sosial dan Manajemen STIAMI, 2016)
The purpose of this study was to analyze how much influence human capital investment, organizational climate with employee performance and its impact on SFM either partially or simultaneously. This research study was conducted on employees of PT. Kalimantan Satya Kencana (PT. CWC) in West Kalimantan. PT. KSK is a company engaged in the management of forestry. The data used is primary data, collecting by direct interviews and filled out the questionnaire to 58 employees. The analytical method used is Path Analysis (Path Analysis) and processed with SPSS 17 software.The analysis showed that the significant and simultaneous human capital investment and organizational climate direction (positive) on the performance of employees with the coefficient of determination (R ²) of 17.6%. With this method of trimming that employee performance and organizational climate significantly and simultaneously direct influence and direction (positive) on the Performance of SFM, while the human capital investment indirect effect on the SFM with the coefficient of determination (R ²) as a whole amounted to 44.28%. These findings indicate that in order to meet and improve SFM, PT. KSK need to pay attention to factors of human capital investment, organizational climate and employee performance because of these factors shown to affect the success of the acquisition of certificates of SFM.